Differentiation of rat full term amniotic fluid stem cells into dopaminergic neurons phenotype via adherent and non-adherent neural induction protocols - Hamzah, Siti Nurusaadah; Vidyadaran, Sharmili; Nordin, Norshariza (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2014)
Recent studies have demonstrated the ability of midterm human amniotic fluid cells to generate dopaminergic (DA) neurons where none using amniotic fluid cells from full term pregnancies has been published. We have established rat AFS cell lines from full term pregnancies, where characteristics of highly potent cells were observed with their ability to differentiate into derivatives representing the three primary germ layers including neural cells. Here we aimed to explore the differentiation potential of our newly established rat full term AFS cells to differentiate into DA neurons phenotype in vitro. Neural-like cells expressing mature and DA neurons phenotype were successfully derived using two established protocols of adherent and non-adherent neural induction assays. These findings have provided us an insight into the use of full term AFS cells as a valuable tool in cell replacement therapy for neurodegenerative diseases such as Parkinson’s disease (PD)